Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pengunjung New Rivermoon di Desa Pusur, Kabupaten Klaten - Subeni, Fajar; Febriyanti, Ria Rahmani Nur (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
This research was conducted at New Rivermoon, Pusur Village, Klaten. This study aims to understand and analyze the effect of facilities and service quality on visitor satisfaction at New Rivermoon. This research is quantitative research. The data used is primary data with data collection methods through questionnaires, observations, and interviews. The sample utilization for research amounted to 100 respondents. The use of data analysis includes validity and reliability testing, classical assumption testing, hypothesis testing and multiple linear regression testing with the help of the SPSS 25 program. The results of this study indicate that facilities and service quality have a positive and significant effect on visitor satisfaction at New Rivermoon visitors.